Independent designers and the future of sustainable fashion: A qualitative inquiry - Zou, Chang; Abdullah, Qistina Donna Lee; Jalil, Marzie Hatef (Edelweiss Applied Science and Technology, 2025)
This study aims to investigate how independent designer labels incorporate sustainable design methods into their products, thus allowing designers to contribute to the development of sustainable products. The study was conducted through qualitative interviews with eight independent designers in Beijing, China. The results were analyzed thematically to conclude how independent designers incorporate sustainable design methods into their designs and the challenges that independent designers face when practicing sustainable design and dealing with them. This paper explores the relationship between designers and sustainable design from three perspectives. Firstly, designers, as key factors in the transition of the apparel industry towards sustainability, have found from the concept and evolution of sustainable fashion that the right design approach plays a vital role in the environmental, economic, and social factors of the product cycle. Secondly, the researchers look at the perspective of independent fashion brand designers’ labels, how they are confronted with sustainability issues, and how designers are improving, how designers are facing the challenges of sustainable design in the future, and how to integrate sustainable design methods into their labels.